Sir Dudley North’un hayatı, iktisat düşüncesi ve 17. yüzyıl Osmanlı ticarî hayatına dair gözlemleri - Aydın, Fatih Baha (My University, 2022)
Bu çalışmada, 1661-1680 yılları arasında İstanbul ve İzmir’de ticaret yapmış Levant Kumpanyası tüccarı Sir Dudley North’un Osmanlı ticarî hayatına dair izlenimleri konu edilmiştir. Bunun için Levant Kumpanyası arşivindeki iş yazışmaları başta olmak üzere muhtelif evraktan, North aile evrakından, İngiliz tüccarın muhasebe defterlerinden ve , tutmuş olduğu notlardan faydalanılmışıtr. Aynı zamanda önemli iktisadi düşünürlerden biri olan Sir Dudley North’un özellikle İstanbul yıllarındaki tecrübesi, sonrasında kaleme alacağı iktisadi metinlerin de temeli olmuştur. 17. yüzyıldaki Osmanlı iktisadi pratiklerinin, İngiliz düşünürün yazılarında yer bulduğu, dolayısıyla Osmanlı iktisat düşüncesinin İngiliz liberal ekonomi yazınına etkisi tartışılmıştır.

In this study, the observations of Sir Dudley North, a Levant Company merchant who traded in Istanbul and Izmir between 1661 and 1680, on the Ottoman commercial life were discussed. For this, various documents, especially business correspondence in the archive of the Levant Company, North family documents, and the British merchant’s personal notes including his ledger and journal were used. At the same time this study showed that Sir Dudley North’s, who is one of the important early economic thinkers, experience in Istanbul, has been the basis of the economic phamplets he wrote later in his career. 17th century Ottoman economic practices took a signifcant place in the writings of the English thinker. Thus the effect of the Ottoman economic thought on the English liberal economy literatüre was also discussed.
Keywords: 17. yüzyıl Osmanlı ticarî hayatı Sir Dudley North; 17. yy; 17th century; 17th century Ottoman commercial life; Economic conditions; Economics; Ekonomi; Ekonomik durum; Finance; Foreign trade in the Ottoman Empire; History; Maliye; mercantilism; merkantilizm; Osmanlı iktisat düşüncesi; Osmanlı’da dış ticaret; Ottoman economic thought; Sir Dudley North; Sir Dudley North, 1641-1691; Tarih; Turkey; Türkiye